Crave - Llovet, Maria, 1982- (Image Comics, 2024)
"CRAVE, a mysterious app that promises to make your desires come true, spreads among the students of an elite university who use it as a hookup app. David, a top student, engages in a game of seduction with the unattainable Alexandra. But as requests to the app escalate and wreak havoc on campus, David and his friends' only chance to stop this spiral is to find out what really lies behind Crave"--Rear cover.